Preferences Over Joint vs. Individual Asset Rights - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Individual-level surveys collecting data on asset ownership have increasingly emphasized eliciting answers regarding whether the ownership or management of the asset is individual or joint. There is often an implicit assumption that individual ownership is better, potentially more empowering, than joint ownership. But the data don’t provide insights on to whether the respondent would prefer to own and/or manage assets jointly or individually. This tool, Preferences over Joint vs. Individual Asset Rights, allows us to elicit responses regarding subjective assessments of the well-being of a hypothetical married individual based on whether they own and/or manage assets individually or jointly. The module may be asked about different types of assets such as agricultural land, livestock, or a dwelling. To fully understand ownership and management preferences, it is useful to have this tool as part of a survey with individual ownership module. This data study includes following files. 1. A survey document (including implementation guidelines). 2.Two files, CAPI_Choices and CAPI_Survey, along with the accompanying help files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with help files, for constructing a CAPI program ready for survey implementation.